Chest Radiograph–based Algorithm for Managing Malfunctioning Ports - Nadolski, Gregory; Shlansky-Goldberg, Richard D.; Stavropoulos, S. William; Soulen, Michael C.; Farrelly, Cormac; Trerotola, Scott O. (Journal of vascular and interventional radiology, 2013)
To evaluate a chest x-ray–based algorithm for managing malfunctioning ports. A review of interventional radiology procedures on malfunctioning ports during the period 2000–2012 was performed. Events were divided into two periods: before and after implementation of an algorithm beginning with tip position evaluation using a chest x-ray. Time to return to usability, frequency of interventions to restore function, and frequency of malfunctioning ports remaining in use after the procedure were calculated. The review included 303 procedures before implementation of the algorithm on 237 access sites in 227 patients (mean age, 56 y; 38% male) and 155 procedures after implementation of the algorithm on 131 access sites in 130 patients (mean age, 55 y; 35% male). Implementation of the algorithm was associated with significantly fewer repeat checks on the same access (27% before algorithm, 9% after algorithm, P < .001) and reduced frequency of a malfunctioning port remaining in use after the interventional radiology procedure (43% before algorithm to 14% after algorithm, P < .001). Median time from consultation to revision was significantly less after implementing the algorithm (13 days before algorithm, 1 day after algorithm, P < .001). Median time from consultation to port usability was also less after implementing the algorithm (2.7 days before algorithm, 1 day after algorithm, P < .001). Implementation of the algorithm was associated with significantly less frequent repeat procedures on the same port and a lower frequency of malfunctioning ports remaining in place. Use of the algorithm was associated with significantly reduced time from consultation to revision and to return to usability. These findings suggest the algorithm allows triage of patients with malfunctioning ports to the appropriate intervention before undergoing a procedure.